Penataan Food Court Di Taman Jalur Taluk Kuantan dengan Pendekatan Arsitektur Tepian Air - Tria Yufani; Muhammad Rijal; Wahyu Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Taman Jalur is one of the recreational destinations in Teluk Kuantan, which is located on the edge of the Batang Kuantan River, Teluk Kuantan, Kuantan Singingi Regency, Riau. There are many people who carry out activities in the park make them take small business in the park of area. This causes in disorder of the lane park area, it makes some troubles, that are circulation, open space, land use, a pedestrian, and parking area. To overcome this problem, a special culinary arrangement is needed as a forum for street vendors to sell which will not only solve culinary problems but also problems outside of culinary that have a direct impact on Taman Jalur as a landmark of Teluk Kuantan City. The arrangement of the Food Court uses a Waterfront Architecture approach which basically has the principle of protecting the edge river area and developing its potentials that can improve human interaction with the natural surroundings in a design that refers to the function of structuring culinary and recreational tourism.Keyword : Taman Jalur, Food Court, Waterfront Architecture